2017
DOI: 10.3233/bmr-150500
|View full text |Cite
|
Sign up to set email alerts
|

Update on the effects of graded motor imagery and mirror therapy on complex regional pain syndrome type 1: A systematic review

Abstract: Graded motor imagery (GMI) and mirror therapy (MT) is thought to improve pain in patients with complex regional pain syndrome (CRPS) types 1 and 2. However, the evidence is limited and analysis are not independent between types of CRPS. The purpose of this review was to analyze the effects of GMI and MT on pain in independent groups of patients with CRPS types 1 and 2. Searches for literature published between 1990 and 2016 were conducted in databases. Randomized controlled trials that compared GMI or MT with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 38 publications
3
51
0
7
Order By: Relevance
“…This may have relevance to rehabilitation, particularly where lower limb CRPS patients perceive the limbs as heavy and weak, which may contribute to the gait impairment that is often observed in CRPS population (Galer et al, 1999). Visual manipulation is established in CRPS treatment in mirror visual feedback therapy (Méndez-Rebolledo et al, 2016), and in therapies using prisms (Moseley et al, 2013). There is potential to combine manipulation of auditory and visual stimuli in the treatment of CRPS and future work would be needed to discover if this is practical, and offers the potential for a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…This may have relevance to rehabilitation, particularly where lower limb CRPS patients perceive the limbs as heavy and weak, which may contribute to the gait impairment that is often observed in CRPS population (Galer et al, 1999). Visual manipulation is established in CRPS treatment in mirror visual feedback therapy (Méndez-Rebolledo et al, 2016), and in therapies using prisms (Moseley et al, 2013). There is potential to combine manipulation of auditory and visual stimuli in the treatment of CRPS and future work would be needed to discover if this is practical, and offers the potential for a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Este factor también pudo haber incidido en la intensidad del dolor y funcionalidad al momento del ingreso. Ambas terapias son un pilar fundamental en la mejoría de la función en pacientes con SDRC (14,15) sobre todo en pacientes con SDRC 1 de evolución prolongada (> a 12 meses) (14).…”
Section: Resultsunclassified
“…Basado en las recomendaciones de las revisiones y sistemáticas y guías clínicas de práctica clínica, el manejo terapéutico del SDRC 1, debe incluir intervenciones interdisciplinarias. El objetivo principal es restaurar la funcionalidad, a través de educación y rehabilitación física con movilización gradual de la extremidad, hidroterapia, terapia de espejos e imaginería motora (6,(14)(15)(16). Se debe abordar además aspectos psicológicos y el alivio del dolor (5,13).…”
Section: Introductionunclassified
“…A study using mirror therapy has shown how this type of visual feedback is effective in reducing pain and enhance motor functionality in the affected limb of stroke patients with complex regional pain syndrome (CRPS) type 1 [40]. A recent review has reported how both graded motor imagery and mirror therapy can improve pain in CPRS type 1 patients, although the authors pointed out that results are not conclusive [41].…”
Section: Multisensory Feedback and Body Representationmentioning
confidence: 99%